Design of A Service Landscape for an ICU Nursing Care Information System Based on Trauma Assessment and SBAR Using an Enterprise Architecture Planning Approach - Ramandhita Aulia Wardany; Faiza Renaldi; Irma Santikarama (Riviera Publishing, 2026)
The increasing complexity of healthcare services requires information systems capable of integrating clinical processes, data, and applications in a structured and sustainable manner. In Intensive Care Units (ICUs), fragmented documentation and limited alignment between nursing services and information systems remain challenges that may affect information accessibility and continuity of patient care. This study aimed to design a Service Landscape for an ICU nursing care information system using the Enterprise Architecture Planning (EAP) approach integrated with The Open Group Architecture Framework Architecture Development Method (TOGAF ADM) up to Phase C. This research employed a qualitative case study method conducted in the ICU of Oto Iskandar Hospital, Nata Soreang. Data were collected through observation, interviews, document analysis, and shadowing of nursing care processes. The proposed architecture was developed by identifying business services, data requirements, and application components based on Trauma Assessment and SBAR (Situation, Background, Assessment, Recommendation) information structures. The results produced five core business services, namely Admission Service, Monitoring Service, Assessment Service, Handover Service, and Transfer Service, which were mapped into Business Architecture, Data Architecture, Application Architecture, and a Service Landscape blueprint. Validation using the TOGAF Architecture Capability Maturity Model (ACMM) obtained an average score of 4.03, categorized as Level 4 (Managed). The findings indicated that the proposed Service Landscape provided consistent traceability among services, data entities, and application modules. This research concluded that the developed blueprint could serve as a conceptual reference for designing integrated and adaptable ICU nursing information systems.